Whole animal freeze-fracture scanning electron microscopy: an easy-to-use method to investigate cell type morphology of marine embryos and larvae - Paganos, Periklis; Caccavale, Filomena; Cocurullo, Maria; D’Aniello, Enrico; Arnone, Maria Ina; Benvenuto, Giovanna (Frontiers in Ecology and Evolution, 2023)
Morphological and molecular characterization of cell types, organs and individual organisms is essential for understanding the origins of morphogenesis. The increased implementation of high throughput methods as a means to address cell type evolution, during the last decade, created the need for an efficient way to assess cell type morphology. Here in order to create a new tool to study cell type morphology, we optimized a fast and easy-to-use whole animal freeze-fracture scanning electron microscopy (WAFFSEM) method. This method was applied on marine experimental systems (echinoderms, mollusks, tunicates, cephalochordates), that have been widely used to assess environmental, developmental and evolutionary questions. Our protocol does not require any specialized equipment and the processed specimens are compatible with scanning electron microscopy. This protocol was able to successfully expose the internal cell types of all specimens in which it was tested and to reveal their cellular and subcellular characteristics. We strongly believe that the combination of our protocol with other methods (e.g., light microscopy and single cell transcriptomics) will be beneficial to further improve the way to classify and describe cell types.